Study of power quality at the point of common coupling of a low voltage grid and a distributed generation system of 7.8 kWp in a tropical region - Granja, Agustín Valverde; Miguel De Souza, Teófilo [UNESP]; Sobrinho, Pedro Magalhães [UNESP]; Santos, Daniel Felipe Arévalo (MDPI, 2018)
In this paper we analyze an experimental 1000 kWh/month distributed generation system in a tropical region connected to a point of common coupling in a low voltage grid that was characterized according to NTC 5001. This photovoltaic system has 7.8 kWp and uses 30 polycrystalline silicon-panels of 260 Wp each. Its maximum energy produced was 850 kWh/month, equivalent to 72.65% of the installed capacity. Finally, there was an increase of 2% with respect to the minimum voltage value that was recorded. The voltage unbalance decreases between 3.5 and 70% and voltage harmonics in each line increased by 7% on line U1, 0.8% on U2, 3% on U3 and current harmonics have a 22% increase. Likewise, the total active and reactive power were increased by 58% and 42% respectively, and the thermography study allowed to establish a temperature increase at the point of common coupling of 7.5%. Therefore, it is expected that this paper can serve as a reference for the application of Colombian law 1715 in solar energy.
Keywords: Experimental network; Low voltage; Power quality; Solar energy